Analisis Kemampuan Pemecahan Masalah Siswa Kelas V SD Negeri 03 Bengkayang pada Mata Pelajaran IPAS - Aprasela, Misel; Silvester, Silvester (STKIP HARAPAN BIMA, 2025)
This study aims to describe students problem solving skills in solving story problems on water cycle material. Problem solving ability consists of 4 indicators, namely: 1) understanding the problem, 2) making a plan, 3) implementing the plan, 4) checking back. The research was conducted in the fifth grade of SD Negeri 03 Bengkayang. The sample in this study were 33 students, but the focus of this study was on subjects totaling 9 students. Data collection techniques using problem solving ability tests and interviews. Data analysis techniques in this study include data collection, data reduction, presenting data and verifying data. The results showed that of the number of fifth grade students, 8 students (24.2%) were in the high score category, 9 students (27.3%) were in the medium score category and 16 students (48.5%) were in the low score category. It can be seen from this study that the problem solving ability of students in the high score category has fulfilled 4 indicators of problem solving ability, namely indicators 1, 2, 3, 4. Students in the medium score category were able to fulfill 3 of the 4 indicators of students' problem solving ability, namely indicators 1, 2, 3. While students in the low score category were only able to fulfill 2 indicators of problem solving ability, namely indicators 1 2.